Trends and hotspots in acupuncture treatment of rat models of stroke: a bibliometric analysis from 2004 to 2023 - Li, Song; Huang, Zhilin; Zhu, Tao; Dai, Anhong; Chen, Xu; Yang, Xiaolin; Zhou, Li; Chen, YiZhou; Shi, Jing (Frontiers in Neuroscience, 2024)
Background Acupuncture is a widely used clinical treatment method, and studies have confirmed its therapeutic effects on stroke patients. It can also reduce the burden on patients and society. Acupuncture treatment is a complementary and preventive treatment for stroke. However, there has yet to be a visual bibliometric analysis of the field of acupuncture for stroke rat models. This study explores future trends, research hotspots, and frontiers in acupuncture for stroke rat models over the past 20 years through investigation and visualization.Methods: We collected literature data on acupuncture treatment of stroke in rats from the Web of Science Core Collection (WOSCC) database from January 1,2004, to December 31,2023. Import into CiteSpace (version 6.2.R4) and RStudio for analysis by author, country/region, affiliation, annual publication, keywords, and journal visualization. Results: A total of 379 articles were retrieved, including articles from 16 countries,258research institutions, and 123 academic journals. The countries and institutions with the most publications were the People's Republic of China （338） and the Fujian University of Traditional Chinese Medicine （43）. Tao, Jing had the highest number of co-citations （144）. The keywords and co-citation clustering show the main research directions in the field, including "artery occlusion," "neural regeneration,""stimulation,""rapid tolerance,""receptor," "signaling pathway," "apoptosis," "oxidative stress," "inflammatory response," "endogenous neurogenesis," "tolerance of local cerebral ischemic tissues," "proliferation of reactive astrocytes" and "neuroprotective effect." The intervention combines classical acupuncture treatment and modern technology (electricity) with electroacupuncture as a new intervention modality. Conclusion:This study demonstrates the increasing research on acupuncture for treating stroke in rat models. The country/region with the most publications is the People's Republic of China. However, international cooperation still needs to be improved, and future researchers must strengthen international cooperation. In addition, in future studies, researchers should improve the overall quality of research results in this area and enhance research protocols.